2018
DOI: 10.1002/jclp.22680
|View full text |Cite
|
Sign up to set email alerts
|

The impact of accommodating client preference in psychotherapy: A meta‐analysis

Abstract: Client preferences in psychotherapy reflect specific conditions and activities that clients desire in their treatment, with increasing evidence pointing to preference accommodation as facilitating psychotherapy outcomes. This updated meta-analysis establishes the magnitude of the effect of client preference accommodation in psychotherapy. Based on data from 53 studies and over 16,000 clients, preference accommodation was associated with fewer treatment dropouts (OR = 1.79) and more positive treatment outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(219 citation statements)
references
References 20 publications
3
176
1
6
Order By: Relevance
“…SDM includes several types of clinician behaviours that take place within patient‐clinician interactions, including (a) identifying and explaining the problem; (b) presenting treatment options and discussing the risks, benefits, and evidence regarding each option; (c) clarifying patient values, preferences, and resources; and (d) and making or deferring a decision . The utility of various SDM components have been extensively studied in the psychotherapy literature, including patient preference accommodation and collaboration between the patient and clinician . In terms of patient preferences within mental health interventions, research indicates that patients not only have inclinations regarding the specific type of treatment that they would like to receive (ie, psychotherapy versus medication), they also have preferences about the characteristics of the clinician that they would like to work with (eg, age, gender, sexual orientation, and personality) and about the methods by which the treatment is implemented (eg, active versus passive patient involvement) .…”
Section: Research Support For Sdm In Mental Health Carementioning
confidence: 99%
See 2 more Smart Citations
“…SDM includes several types of clinician behaviours that take place within patient‐clinician interactions, including (a) identifying and explaining the problem; (b) presenting treatment options and discussing the risks, benefits, and evidence regarding each option; (c) clarifying patient values, preferences, and resources; and (d) and making or deferring a decision . The utility of various SDM components have been extensively studied in the psychotherapy literature, including patient preference accommodation and collaboration between the patient and clinician . In terms of patient preferences within mental health interventions, research indicates that patients not only have inclinations regarding the specific type of treatment that they would like to receive (ie, psychotherapy versus medication), they also have preferences about the characteristics of the clinician that they would like to work with (eg, age, gender, sexual orientation, and personality) and about the methods by which the treatment is implemented (eg, active versus passive patient involvement) .…”
Section: Research Support For Sdm In Mental Health Carementioning
confidence: 99%
“…Eliciting and accommodating each of these types of preferences has been shown to enhance patients' experiences in psychotherapy in several ways, including improving their satisfaction with treatment, increasing their levels of hope, and fostering a stronger alliance with their clinicians . In addition, recent meta‐analyses have indicated that including patient choice in psychotherapy results in higher retention rates and more positive treatment outcomes . Similarly, results from a recent meta‐analysis suggest a positive association between collaboration, defined as active clinician and patient participation in psychotherapy, and treatment outcomes .…”
Section: Research Support For Sdm In Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Patient beliefs and expectations about treatment have a significant impact on the development of early treatment alliance and the ultimate outcome of therapy (Constantino, Coyne, Boswell, Iles, & Vîslă, ). We can better integrate research evidence into clinical practice if the wishes of the patient are taken into account (Swift et al, ). Careful therapeutic attending and responsiveness to patient preferences, expectations, and anxieties are essential for providing tailored mental health services that take into account all three areas of EBP (Coyne, Constantino, & Muir, ; Walter, Turner, Macaskill, McCaffery, & Irwin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be important for psychotherapists to first assess what their patient knows about psychotherapy, and second, what they would prefer to happen in their psychotherapy. Engaging patients in treatment decisions can lead to a more appropriate and cost‐effective use of health services and better health outcomes (Swift, Callahan, Cooper, & Parkin, ).…”
Section: How Do Ests Mitigate Patient Anxieties?mentioning
confidence: 99%